Cyberbullying in the Age of Social Media: A Systematic Review of Mental Health Outcomes among Adolescents - Fathiariani, Liza; Martina, Martina; Zahra, Zulfa (Asian Journal of Public Health and Nursing, 2025)
Background: Cyberbullying via social media has emerged as a major public health concern among adolescents; however, evidence regarding its impact on mental health remains fragmented. This systematic review aimed to synthesize empirical evidence published between 2016 and 2025 on the association between social media–based cyberbullying and adolescent mental health outcomes. Methods: A systematic review was conducted using PubMed, ScienceDirect, Scilit, and PsycINFO in accordance with PRISMA 2020 guidelines. Studies were eligible if they included adolescents aged 10–19 years, explicitly examined cyberbullying within social media contexts, and assessed mental health outcomes using validated instruments. Risk of bias was evaluated using the Newcastle–Ottawa Scale (NOS) and Joanna Briggs Institute (JBI) appraisal tools. Results: Twenty-three studies involving more than 38,000 adolescents were included, comprising cross-sectional, longitudinal, and mixed-design studies. Reported prevalence of cyberbullying ranged from approximately 10% to 74.5%. Cybervictimization was consistently associated with increased risks of depression (OR ≈ 1.4–2.3), anxiety (OR ≈ 1.8–2.0), and suicidal behaviors (AOR = 2.62; 95% CI 1.73–3.98). Longitudinal evidence indicated that cybervictimization often preceded deterioration in mental health outcomes. Anxiety, peer relational stress, and sleep problems emerged as key mediating factors, while self-control and school connectedness appeared to serve as protective factors. Conclusions: Cyberbullying represents a significant and consistent risk factor for adverse mental health outcomes among adolescents. These findings highlight the need for comprehensive prevention strategies, including school-based interventions, digital literacy programs, and strengthened social media platform safeguards.